ダイ10ジ ナンキョク カンソクヨウ KD60カタ セツジョウシャ ノ ソウオン ソクテイ - 芳野, 赳夫; ヨシノ, タケオ; 熊本, 芳朗; クマモト, ヨシロウ; 稲垣, 勝之; イナガキ, カツユキ; YOSHINO, Takeo; KUMAMOTO, Yoshiro; INAGAKI, Katsuyuki (国立極地研究所, 1970)
P(論文) Acoustical noises in two diesel-engine driven KD60 oversnow vehicles (KD607 with all-over cab and KD608 with cab only over driver's seat) to be used by the 10th Japanese Antarctic Research Expedition (1968-1970) were measured in October 1968, during the test run of vehicles (inside and outside) and during the idling (inside), on volcanic deposits at the foot of Mt. Fuji. Instrument used is an Impulse Precision Sound Level Meter (type 2203 made by Bruel and Kjaer, in Denmark). The noises were measured when the engine was operating at 1500-2400 rpm at a speed of 10-18 km/h during the test run, and at 600, 1000, 1500, 2000 and 2400 rpm during the idling. There are five measuring spots inside the KD607 and one spot outside, and two spots inside the KD608. The maximum noise levels of running KD607, represented by A-Scale of the Level Meter, are 93dB inside the cabin and 96dB outside, and 100dB in KD608. The maximum noise levels when idling the engine at 2400 rpm are 81.5dB and 86dB in KD607 and KD608, respectively. The noise intensity inside the cabin during the running is below safe level given by the International Organization for Standardization, Technical Committee 43 Acoustics, except in the domain of low frequency. Ordinary conversation with somewhat loud voices is possible during the idling, but when the vehicles is running only shouts are audible. departmental bulletin paper